Membangun Literasi Digital Bagi Warga Desa Hurung, Kecamatan Banama Tingang, Kabupaten Pulang Pisau - Enny Dwi Oktaviyani; Ariesta Lestari; Licantik Licantik (Jurnal Nasional Pengabdian Masyarakat, 2021)
Digital literacy is defined as the ability to understand and use information in various forms from various sources accessed through computer devices. Digital literacy will create a society with a critical-creative mindset and views. Provocative issues will not easily consume it, become victims of hoax information, or victims of digital-based fraud. Residents of Hurung Village, Banama Tingang District, Pulang Pisau Regency are partners in this community service activity who are active users of digital technology via mobile phones to access the internet and interact with other people. However, in digital technology, partners have not been able to distinguish true or false information and forward information obtained from social media or unclear sources. Likewise, in the search for information, still using sources or references that are not valid. So that the information obtained cannot be justified. In this service activity, the service team created digital media using a village profile website to support digital literacy for Hurung village. The activity was carried out in three stages, namely material presentation, mentoring, and training on the use of village profile websites. With this activity, it is hoped that it can be helpful to add insight, knowledge and build Hurung village to become a pioneer village of digital literacy